Bridge to terabithia - Paterson, Katherine; Diamond, Donna (New York : HarperEntertainment, 2007)
The life of ten-year-old Jess in rural Virginia expands when he becomes friends with newcomer Leslie, and they create the imaginary land of Terabithia where they rule as king and queen, until a terrible tragedy occurs. Includes a reader's guide with discussion questions.
Keywords: Friendship -- Fiction; Grief -- Fiction; Death -- Fiction; Virginia -- History -- 20th century -- Fiction